Docking Studies and Molecular Dynamics Simulation of Compounds Contained in Kaempferia Galanga L. to Lipoxygenase (LOX) for Anti-Inflammatory Drugs - Supandi; Yeni; Lusi Putri Dwita (Journal of Mathematical and Fundamental Sciences, 2021)
Inflammation is a self-protective response to start the healing process. An anti-inflammatory target worth developing are lipoxygenase inhibitors, which have been studied for several diseases, including severe respiratory disease. This research had the goals of estimating the activity of 21 compounds from K. galanga to inhibit the lipoxygenase (LOX) and estimating the bond stability of the ligand-LOX complex. Based on the compound’s affinity for LOX, the compounds in K. galanga were selected by utilizing the PLANTS docking software, with zileuton as the reference ligand. The GROMACS application was used to simulate the molecular dynamics of the LOX-ligand complex at 310 K. Based on the chemPLP score, most of the 21 K. galanga compounds showed a higher affinity towards 5-LOX compared to zileuton. δ-3-carene had the best affinity for 5-LOX. In the simulation of molecular dynamics until 20 ns, the RMSD of δ-3-carene and 5-LOX was not more than 0.03 nm or 0.3 Å, indicating that the whole system showed decent stability and had ‑1.67392 x 106 kcal/mol as the average potential energy. The results showed that K. galanga contains active components of 5-LOX inhibitors that could be developed.